2020
DOI: 10.1002/slct.202003766
|View full text |Cite
|
Sign up to set email alerts
|

The Properties and SCR de‐NOx Application of Supported V2O5/TiO2 Catalysts with Different Polymerization State of VOx Species Controlled by the pH Value of Their Precursors

Abstract: NO x is the main pollutant in the air, which causes many harmful effects on society. The V 2 O 5 /TiO 2 catalysts are very important to reduce the NO x from the heat engine plants and vehicle exhausts. However, various reasons will affect the performance of the catalysts. In this paper, the polymerization state of surface VO x of supported V 2 O 5 /TiO 2 catalysts was controlled by changing the pH value of the impregnation precursor solutions, and the redox and acidity properties of the catalysts can be adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…We then performed 51 V MAS NMR analyses to quantitively determine the different vanadyl species. Benefiting from sufficiently high fields and fast spinning rates, 51 V MAS NMR can provide detailed information on the local environment of the vanadyl species. As shown in Figures and S11, the pristine VWT catalyst exhibited three vanadyl species: monomeric, dimer, and oligomer vanadyl species. For the VWT catalyst, the bands at 510 and 542 ppm were attributed to the monomer VO x structure (13.0%), while the band at 581 ppm was assigned to the dimeric vanadia structure (37.5%).…”
Section: Resultsmentioning
confidence: 99%
“…We then performed 51 V MAS NMR analyses to quantitively determine the different vanadyl species. Benefiting from sufficiently high fields and fast spinning rates, 51 V MAS NMR can provide detailed information on the local environment of the vanadyl species. As shown in Figures and S11, the pristine VWT catalyst exhibited three vanadyl species: monomeric, dimer, and oligomer vanadyl species. For the VWT catalyst, the bands at 510 and 542 ppm were attributed to the monomer VO x structure (13.0%), while the band at 581 ppm was assigned to the dimeric vanadia structure (37.5%).…”
Section: Resultsmentioning
confidence: 99%
“…Compared to our previous studies on catalysts TiO 2 and MnOx, V 2 O 5 is widely used in lithium-ion batteries, [28][29][30] supercapacitors, 31,32 gas sensitive sensor, 33,34 electrochromic materials 35,36 and catalytic destruction of hazardous organic compounds [37][38][39][40] owing to its abundant valence state (+2, +3, +5) as well as various chemical structures. 41 Researchers mainly adopted the sol-gel, 42 electrodeposition, 43 hydrothermal, 44 and magnetron sputtering 45,46 methods to prepare V 2 O 5 films. Due to its dense and uniform structure as well as excellent adhesion forces between the coating and substrate, the coating prepared by the magnetron sputtering method has received widespread attention.…”
Section: And Nhmentioning
confidence: 99%
“…The transition metal TiO 2 can adjust the acidity of the surface through the formation of oxygen defects and changes in the acid density of Ti. For example, doping TiO 2 with metal oxides, such as SiO 2 , ZrO 2 , WO 3 , Al 2 O 3 , and V 2 O 5 , has been reported to increase the acidity of the surface and catalytic activity [18][19][20][21][22]. In addition, studies have reported the modification of the surface of TiO 2 by introducing functional groups via chemical treatment such as PO 4 3and SO 4 2- [23][24][25].…”
Section: Introductionmentioning
confidence: 99%